Preparation of Spin-Coated Poly(vinyl alcohol)/ chitosan/ Gold Nanoparticles Composite and Its Potential for Colorimetric Detection of Cyanide in Water - Budlayan, Marco Laurence M (Archīum Ateneo, 2022)
The rampant use of cyanide in mining activities has posed a substantial hazard to aquatic ecosystems and human health. Herein, a composite film of poly(vinyl alcohol)/chitosan (PVA/CS) with gold nanoparticles was synthesized as a potential colorimetric sensor for cyanide ions detection in water. The utilized AuNPs with a mean diameter of 14.32±3.49 nm were synthesized by chemical reduction using polyethyleneimine. Ultraviolet-visible spectroscopy revealed the characteristic peak of AuNPs at around 530 nm in the spectrum of PVA/CS/AuNP film, while SEM microscopy revealed the integration AuNPs across the polymer substrate. A color change from red to colorless was observed on the composite film after the addition of water samples with cyanide ions with a visual detection limit between 0.1-1 ppm. The sensor also exhibited good selectivity towards cyanide against the tested water samples containing various metal ions. This study reveals the potential of the fabricated PVA/CS/AuNP composite film as a simple, affordable, and environmentally benign material for on-site detection of cyanide in water and other related application.